Headaches in patients with previous head injuries: A population-based historical cohort study (HUNT). (October 2016) - Nordhaug, Lena Hoem; Vik, Anne; Hagen, Knut; Stovner, Lars Jacob; Pedersen, Torunn; Gravdahl, Gøril Bruvik; Linde, Mattias
Background: Headache attributed to head injury is claimed to be among the most common secondary headache disorders, yet available epidemiological evidence is scarce. We evaluated the prevalence of headache among individuals previously exposed to head injury by a comparison to an uninjured control group. Methods: This population-based historical cohort study used data from hospital records on previous exposure to head injury linked to a large epidemiological survey with data on headache occurrence. Participants without head injury, according to hospital records, were used as controls. The head injuries were classified according to the Head Injury Severity Scale (HISS) and the International Classification of Headache Disorders (ICHD-3 beta). Binary logistic regression was performed to investigate the association between headache and head injury, controlling for potential confounders. Results: The exposed group consisted of 940 individuals and the control group of 38, 751 individuals. In the multivariate analyses, adjusting for age, sex, anxiety, depression and socioeconomic status, there were significant associations between mild head injury and any headache, migraine, chronic daily headache and medication overuse headache. Conclusion: Headache was more likely among individuals previously referred to a hospital for a mild head injury compared to uninjured controls.